Plasma cell targeting with the anti-CD38 antibody daratumumab in myalgic encephalomyelitis/chronic fatigue syndrome—a clinical pilot study - Fluge, Øystein; Rekeland, Ingrid Gurvin; Sørland, Kari; Alme, Kine; Risa, Kristin; Bruland, Ove; Tronstad, Karl Johan; Mella, Olav (Frontiers in Medicine, 2025)
BackgroundMyalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) entails low quality of life for patients and massive societal costs. There is an urgent need for elucidation of disease mechanisms and for rational treatment. Our working hypothesis is that ME/CFS in a subgroup of patients is associated with functional autoantibodies emerging after an infection, and that plasma-cell depletion with transient reductions in serum immunoglobulins will have a beneficial effect on patients’ symptoms.ObjectiveTo evaluate feasibility and toxicity of plasma-cell targeting treatment using the subcutaneous anti-CD38 antibody daratumumab (Darzalex®) in moderate to severe ME/CFS, and to assess the clinical course through 12–24 months follow-up after daratumumab intervention.MethodsWe performed a prospective, open-label pilot trial (EudraCT 2022–000281-18). Ten female patients were enrolled. Following 12 weeks run-in, six patients received four daratumumab injections. The next four patients received four, followed by three additional injections from week 14.ResultsAll planned treatments were administered, and there were no serious adverse events. Four patients had no significant clinical changes. Six patients experienced marked improvement. For all 10 patients, mean SF-36 Physical Function (SF-36 PF) increased from 25.9 to 55.0 at 8–9 months (p = 0.002). DePaul Questionnaire-Short Form (DSQ-SF) symptom scores decreased from 72.3 to 43.1 (p = 0.002). In six responders, mean SF-36 PF increased from 32.2 to 78.3, and DSQ-SF score decreased from 71.1 to 24.3. Five of these six patients had major and sustained improvement with a mean SF-36 PF of 88 (range 80–95) toward end of follow-up. Mean steps per 24 h was 3,359 (range 1,493–6,277) at baseline. At 8–9 months, the mean number of steps was 5,862, and 7,392 in the six responders. All five patients with sustained improvement reached a mean step count above 10,000/24 h for some weeks, and above 15,000 on individual days. Relative reduction of serum IgG levels was 54% in six patients with clinical improvement, and 40% among four with no benefit. Low baseline NK-cell count in blood was significantly associated with lack of clinical response.ConclusionSubcutaneous daratumumab in 10 ME/CFS patients was well tolerated. In six patients, treatment was associated with clinical improvement and concurrent transient reduction of serum IgG levels, indicating important pathomechanistic roles for long-lived plasma cells and functional autoantibodies. No definite conclusions should be drawn before a randomized study has been performed.Clinical trial registrationhttps://euclinicaltrials.eu, Identifier: 2022-000281-18.